Abundant polymorphic transitions in the Al0.6CoCrFeNi high-entropy alloy. (March 2019) - Wang, L.; Zhang, F.; Nie, Z.; Wang, L.; Wang, F.; Wang, B.; Zhou, S.; Xue, Y.; Cheng, B.; Lou, H.; Chen, X.; Ren, Y.; et al.
Abstract: Polymorphism and polymorphic transitions are attracting considerable interest because of their significant effect on the phase stability, switchable properties, and the atomic rearrangement mechanism in materials. Here, by employing in situ high-pressure synchrotron radiation X-ray diffraction, we reveal surprisingly abundant polymorphic transitions in an Al0.6 CoCrFeNi high-entropy alloy (HEA). The original body-centered cubic ( bcc ) phase transfers to an orthorhombic phase at ∼ 10.6 GPa during compression at room temperature, and the orthorhombic phase remains stable up to ∼ 40 GPa. When the lattice stress is released entirely, the orthorhombic phase can further transform into a body-centered tetragonal structure. On the other hand, when the original bcc phase is heated to high temperatures, a face-centered cubic phase forms, and it can further transform to a hexagonal close packing phase by applying pressure. In total, we observed five polymorphs in the Al06 HEA, and they all can exist at ambient conditions. The complex chemistry and the pressure/temperature tuned lattice distortion may play a key role in introducing and stabilizing the rich polymorphs in the Al06 HEA. Our findings may bring new insights into the correlation between lattice distortion and phase stability/transitions of HEAs and help to explore HEAs with novel structures and properties. Graphical abstract: Image 1 Highlights: Single body-centered cubic Al0.6CoCrFeNi high-entropy alloy (HEA) transforms to an orthorhombic phase at high pressure. The orthorhombic phase transforms to a body-centered tetragonal phase after the lattice stress release. Five polymorphs which all can exist at ambient pressure were found in Al06 HEA.